Lipidomics profiles in hepatocytes from nonalcoholic steatohepatitis patients differ markedly from in vitro‐induced steatotic hepatocytes. Issue 11 (28th February 2022) - Kralj, Thomas; Khatri, Raju; Brouwer, Kenneth R.; Brouwer, Kim L. R.; Creek, Darren J.
Abstract : Nonalcoholic steatohepatitis (NASH) is a severe form of liver injury that can be caused by a variety of stimuli and has a significant mortality rate. A common technique to induce in vitro steatosis involves culturing primary human hepatocytes (PHH) in fatty acid‐enriched media. This study compared the lipidome of PHH cultured in fatty acid‐enriched media to hepatocytes from patients with NASH and healthy controls. Hepatocytes from NASH patients displayed increased total cellular abundance of glycerolipids and phospholipids compared to healthy control hepatocytes. PHH cultured in fatty acid‐enriched media demonstrated increased glycerolipids. However, these culture conditions did not induce elevated phospholipid levels. Thus, culturing PHH in fatty acid‐enriched media has limited capacity to emulate the environment of hepatocytes in NASH patients. Abstract : The lipidome of hepatocytes from nonalcoholic steatohepatitis (NASH) patients displays increased abundance of glycerolipids and phospholipids compared to healthy controls. Primary human hepatocytes (PHH) cultured in fatty acid‐enriched media, a common technique for inducing in vitro steatosis, only increased glycerolipids. Thus, culturing PHH in fatty acid‐enriched media has limited capacity to emulate the environment of hepatocytes in NASH patients.